Peningkatan Kemampuan Berpikir Kritis Dan Kreatif Siswa Sma Menggunakan Pendekatan Penemuan Terbimbing - Munawir, Ahmad (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2014)
Entitled Learning Mathematics with Guided Discovery Approach for Improving Critical Thinking Skills, and Creative High School Students, motivated by the lack of ability critical and creative thinking which are complex problems in mathematics learning.This resulted in low student achievement in math mastery.If the condition is left continuously without any attempt to fix, it is concerned that students will not be competent in mastering science and technology demanded by age. Therefore, a variety of efforts, including by implementing guided discovery method in this study. The data were obtained by interviews, questionnaires observation and writing test. The method used is the method of experimental quasi with desain: quasi experimental nonequivalent groups pretest-posttest design in which the experimental group and the control group were not chosen at random. Technique of sampling, form Purposive Sampling, with samples of high school students of class XI Sains. These results indicate that: Implementation of the model learning through approach of guided discovery method provides a positive contribution to the improvement of creative critical thinking ability of mathematics, attitudes, and activities of students, compared with students who study mathematics with conventional learning. Conclusions of research is through approach of guided discovery method can be used as a model of learning to improve thinking ability critical and creative of mathematics, attitudes and activities of students.